PENGARUH PENGGUNAAN BASALT FIBER PADA SIFAT MEKANIS BETON GEOPOLIMER DENGAN KOH SEBAGAI ALKALI AKTIVATOR: PENGARUH PENGGUNAAN BASALT FIBER PADA SIFAT MEKANIS BETON GEOPOLIMER DENGAN KOH SEBAGAI ALKALI AKTIVATOR - Konstatinus Moambura, ayub; Rusfiandi, wandi; nernawani, nernawani (Jurusan Teknik Sipil Polnep, 2023)
Concrete is the most important material in building construction, including bridges, piers and buildings.Concrete is the main raw material in construction nowadays, where wooden construction is starting to beabandonedThis research aims to evaluate the effect of using basalt fiber on the mechanical properties of geopolymerconcrete using KOH as an alkali activator. Geopolymer concrete is an environmentally friendly alternativeconstruction material, which replaces the use of portland cement with a geopolymeric binder. The addition ofbasalt fiber is expected to improve the mechanical properties of geopolymer concrete, namely its compressivestrength.Stages of this research method involve making geopolymer concrete samples with varying compositions,including varying the concentration of KOH as the alkali activator and the percentage of basalt fiber added.These samples will be tested to evaluate their mechanical properties, namely compressive strength, and otherphysical properties. It is hoped that this research will result in a better understanding of the influence of theuse of basalt fiber on the mechanical properties of geopolymer concrete. It is hoped that the results of thisresearch can become a basis for the construction industry to improve the performance of geopolymer concreteby using basalt fiber as reinforcement. Apart from that, this research will also provide new insights into the useof KOH as an alkali activator in geopolymer concrete. Currently, TKT in research has a value of 1, namelyformulating a geopolymer concrete mix design concept and the final target of the results of this research is todemonstrate scientific feasibility through analytical and laboratory studies, proof of concept and geopolymerconcrete products that meet construction material standards.Keywords: geopolymer concrete, basalt fiber, compressive strength, KOH, alkali activator.